Potentially Thrombogenic Materials in Factor IX Concentrates - Kingdon, H. S; Lundblad, R. L; Veltkamp, J. J; Aronson, D. L (Thrombosis and Haemostasis, 1975)
Factor IX concentrates manufactured from human plasma and intended for therapeutic infusion in man have been suspected for some time of being potentially thrombogenic. In the current studies, assays were carried out in vitro and in vivo for potentially thrombogenic materials. It was possible to rank the various materials tested according to the amount of thrombogenic material detected. For concentrates not containing heparin, there was substantial agreement between the in vivo and in vitro assays, with a coefficient of correlation of 0.77. There was no correlation between the assays for thrombogenicity and the antithrombin III content. We conclude that many presently available concentrates of Factor IX contain substantial amounts of potentially thrombogenic enzymes, and that this fact must be considered in arriving at the decision whether or not to use them therapeutically.